Competitividad SEO en las empresas industriales. Una metodología: El caso de la Industria vasca - Jose Luis León Sáez de Ybarra (Atlantic Review of Economics, 2014)
– We present an investigation into two parts to assess the quality of the competitive internet websites of selected industries in the Basque Country. The ad hoc methodology developed for this research can be applied to other regional areas. Competitiveness is defined according to two measurable parameters, first, obtained position in the ranking of Google for each keyword to define a main product or function for customers and second, the SEO quality of each major element of content, such as title page, metadescription, PageRank and others. It shows the comparative or benchmarking of Basque companies in selected sectors with the ranking leaders in Google, in terms of SEO and social media use.
Keywords: L86; M31; 330